Comparing Grids With Vertical and Horizontal Item-by-Item Formats for PCs and Smartphones. (June 2018) - Revilla, Melanie; Couper, Mick P.
Much research has been done comparing grids and item-by-item formats. However, the results are mixed, and more research is needed especially when a significant proportion of respondents answer using smartphones. In this study, we implemented an experiment with seven groups ( n = 1, 476), varying the device used (PC or smartphone), the presentation of the questions (grids, item-by-item vertical, item-by-item horizontal), and, in the case of smartphones only, the visibility of the "next" button (always visible or only visible at the end of the page, after scrolling down). The survey was conducted by the Netquest online fieldwork company in Spain in 2016. We examined several outcomes for three sets of questions, which are related to respondent behavior (completion time, lost focus, answer changes, and screen orientation) and data quality (item missing data, nonsubstantive responses, instructional manipulation check failure, and nondifferentiation). The most striking difference found is for the placement of the next button in the smartphone item-by-item conditions: When the button is always visible, item missing data are substantially higher.